2018
DOI: 10.1016/j.jmbbm.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Improved tribocorrosion performance of bio-functionalized TiO2 nanotubes under two-cycle sliding actions in artificial saliva

Abstract: After insertion into bone, dental implants may be subjected to tribocorrosive conditions resulting in the release of metallic ions and solid wear debris, which can induce to peri-implant inflammatory reactions accompanied by bone loss, and ultimately implant loosening. Despite the promising ability of TiO nanotubes (NTs) to improve osseointegration and avoid infection-related failures, the understanding of their degradation under the simultaneous action of wear and corrosion (tribocorrosion) is still very limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 82 publications
(125 reference statements)
2
25
0
Order By: Relevance
“…After screening full texts, a total of 44 studies were included considering the tribocorrosion analyses for dental implants and frameworks applications. The characteristics of the 44 studies (Vieira et al, 2006;Banu et al, 2008;Richard et al, 2010;Souza et al, 2010aSouza et al, , 2012Sivakumar et al, 2011;Dimah et al, 2012;Mardare et al, 2012;Mathew et al, 2012a,b;Albayrak et al, 2013;Alves et al, 2013Alves et al, , 2014Alves et al, , 2017Alves et al, , 2018Benea et al, 2013Benea et al, , 2015Benea et al, , 2017Licausi et al, 2013a,b;Fazel et al, 2015;Figueiredo-Pina et al, 2015;Golvano et al, 2015;Oliveira et al, 2015;Buciumeanu et al, 2016Buciumeanu et al, , 2017Correa et al, 2016;Guinon Pina et al, 2016;Marques et al, 2016;Mindivan et al, 2016;Pontes et al, 2016;Sampaio et al, 2016b;Silva et al, 2016;Bryant and Neville, 2017;Danaila and Benea, 2017;Mindivan and Mindivan, 2018;Sikora et al, 2018;Trino et al, 2018;Wang et al, 2018;Branco et al, 2019;Corne et al, 2019;Cui et al, 2019a,b;…”
Section: The Relevance Of Bio-tribocorrosion In Dentistry and State Omentioning
confidence: 99%
“…After screening full texts, a total of 44 studies were included considering the tribocorrosion analyses for dental implants and frameworks applications. The characteristics of the 44 studies (Vieira et al, 2006;Banu et al, 2008;Richard et al, 2010;Souza et al, 2010aSouza et al, , 2012Sivakumar et al, 2011;Dimah et al, 2012;Mardare et al, 2012;Mathew et al, 2012a,b;Albayrak et al, 2013;Alves et al, 2013Alves et al, , 2014Alves et al, , 2017Alves et al, , 2018Benea et al, 2013Benea et al, , 2015Benea et al, , 2017Licausi et al, 2013a,b;Fazel et al, 2015;Figueiredo-Pina et al, 2015;Golvano et al, 2015;Oliveira et al, 2015;Buciumeanu et al, 2016Buciumeanu et al, , 2017Correa et al, 2016;Guinon Pina et al, 2016;Marques et al, 2016;Mindivan et al, 2016;Pontes et al, 2016;Sampaio et al, 2016b;Silva et al, 2016;Bryant and Neville, 2017;Danaila and Benea, 2017;Mindivan and Mindivan, 2018;Sikora et al, 2018;Trino et al, 2018;Wang et al, 2018;Branco et al, 2019;Corne et al, 2019;Cui et al, 2019a,b;…”
Section: The Relevance Of Bio-tribocorrosion In Dentistry and State Omentioning
confidence: 99%
“…Therefore, tribocorrosion studies become of fundamental importance, not only because of the high probability of adhesion failure of the nanotubular systems, but also because of their high clinical relevance, since implant degradation in vivo can seriously compromise osseointegration or even its long-term stability. In the attempt to construct effective nanotubular systems based on an integrated and multidisciplinary approach that addresses the development of tribocorrosion resistant implant surfaces with potential to avoid infection, and simultaneously, promote osseointegration, Alves and co-workers have recently reported, for the first time, important findings on the tribocorrosion field [101,102].…”
Section: Modification Of Titanium and Titanium-alloys Surface Featurementioning
confidence: 99%
“…The adhesion properties and degradation mechanisms of TiO 2 NTs were investigated by tribo-electrochemical tests carried out in AS under single and multiple sliding actions, to better mimic real in vivo conditions that dental implants might be exposed to in real life [101,102]. From these studies the poor adhesion of conventional TiO 2 NTs was undoubtedly confirmed, and bio-functionalization came out as a very promising approach to overcome it.…”
Section: Modification Of Titanium and Titanium-alloys Surface Featurementioning
confidence: 99%
See 2 more Smart Citations